Investigating honour-based abuse and other crimes in South Asian communities: the benefits, limitations and impacts of ‘ethnic matching’ and ethnic ‘difference’ of police officers - Aplin, Rachael (Policing and society, 2022)
This article considers the benefits, limitations and potential impacts of ‘ethic matching’ South Asian (SA) police officers to victims, or conversely allocating ‘different’ non-SA officers to reported honour-based abuse (HBA) cases and other crimes. To explore these themes, semi-structured interviews in one English police force with 15 police specialist detectives in Public Protection took place. Lack of cultural competence by some non-SA officers was evident, exposing stereotyping and tokenism. Some professional race anxiety features, but to a lesser extent. Cultural ignorance impacts an officer’s ability to identify crime patterns; results in misconstruing victim perspectives and means that officers may not recognise cues that victims are at risk. The opposing perspective identifies that there are enormous benefits to ‘ethnic matching’ SA officers and victims when investigating crimes, notably enhanced insight due to cultural competence, excellent victim rapport and the use of foreign language skills. Conversely, findings indicate that in exceptional circumstances cultural bias by some same ethnicity officers can act as an impediment, influencing officer decision-making and detrimentally affecting victims’ best interests. Extant literature reinforces the contention that victims do not want to be ‘ethnic matched’ to the police or other professionals, for fear that officials may leak information to the wider community. Albeit there are notable benefits to ethnic matching, factors such as training and experience are equally important. Nevertheless, the article affords valuable insights into the strengths and limitations of ethnic matching and ethnic difference, which will aid operational supervisory police officers when resourcing such incidents.